Exploring patient perspectives on Iran’s Electronic Prescription System: a Qualitative Inquiry - Arabian, Sajed; Zakerabasali, Somayyeh; Raee, Mohammad Javad (Frontiers in Medicine, 2024)
Background: Electronic prescriptions represent a fundamental shift in service delivery, healthcare management, and associated costs, offering numerous advantages. However, akin to other electronic systems, they also present challenges. This study aimed to investigate patients' understanding of the challenges associated with electronic prescriptions in Iran.Methods: This study employed a qualitative research design, utilizing individual and semistructured interviews with patients referred to selected pharmacies across all eleven districts of Shiraz City. The data was analyzed using MAXQDA software (version 10), and descriptive statistics for demographic data were calculated using SPSS version 19.The study revealed that the participants generally demonstrated a certain level of familiarity with electronic prescribing systems. However, it was evident that many were unaware of the potential implications of such technology on their relationships with healthcare providers. This underscores the urgent need for patient understanding in the context of the electronic prescription system. While patients were relatively familiar with the functionality of electronic prescribing systems, they lacked a comprehensive understanding of how using these systems could affect their interaction with healthcare providers.Patients are significant beneficiaries of the electronic prescribing system. By addressing their needs and concerns, they can develop a positive attitude towards this system . Their active engagement can pave the way for the system's ease of use, increase its acceptance, and ultimately enhance the quality of healthcare services.